AB0496 18F-FDG-PET/CT, 11C-METHIONINE-PET/CT AND MULTI-PARAMETRIC MRI IN THE EVALUATION OF DISEASE ACTIVITY AND GLAND FUNCTION IN PRIMARY SJÖGREN'S SYNDROME. (June 2019) - Bombardieri, Michele; Ciurtin, Coziana; Kostapanos, Michalis; Astorri, Elisa; Tappuni, Anwar; Jordan, Natasha; Azeem, Saleem; Fuller, Teresa; Port, Kathleen; Ratia, Nirav; Maurik, Andre van; Gray, Calum; et al.
Abstract : Background: Saliva and tear flow rates and minor salivary gland biopsy are typically used to assess gland function and disease activity in primary Sjögren's syndrome (pSS); however, these have limitations. Imaging methods can directly visualize and generate quantitative values in individual glands. 18 F-FDG-PET/CT ( 18 F-FDG) measures glucose metabolism, a potential surrogate for inflammation; 11 C-methionine-PET/CT ( 11 C-met) is an amino acid PET tracer that assesses protein synthesis, a potential surrogate for gland synthetic function. Objectives: Explore the potential of molecular imaging and multi-parametric MRI to characterize and quantify pSS disease manifestations. Methods: In this pilot imaging study (203818), patients with pSS diagnosed per AECG criteria, with a EULAR Sjögren's syndrome disease activity index score ≥5, and basal salivary flow >0.0 mL/min or stimulated salivary flow rate ≥0.05 mL/min, underwent 18 F- FDG and 11 C–met and dynamic contrast-enhanced and diffusion-weighted MRI, followed by minor salivary gland biopsy for histological analysis. Age- and sex-matched healthy volunteers (HV) underwent MRI and 11 C-met. HV-pSS mean differences (m-diff; 95% confidence intervals [CI]) were calculated and Pearson's correlation coefficients (r) estimated. Peak PET standard uptake values (SUVpeak) were used in the correlations and SUVmax values were recorded. All methods were compared with routine clinical and laboratory tests. Results: 12 patients had MRI, 18 F- FDG and 11 C–met; while HV (n=12) had MRI (n=12) and 11 C–met (n=8). A lower 11 C-met SUVpeak was seen in the parotid (m-diff: 1.4 g/mL [0.4, 2.3]) and submandibular (m-diff: 2.0 g/mL [0.9, 3.2]) glands in pSS versus HV, as was a trend for lower lacrimal gland uptake (m-diff: 0.5 g/mL [-0.2, 1.3]) in patients with pSS. On structural MRI, the fat fraction (mean%) was higher in pSS vs HV in the submandibular glands (m-diff: -14.8 [CI: -29.3, -0.4]), with similar trends observed in the parotid glands (-11.2 [-24.3, 1.9]). There was a negative correlation between 11 C-met uptake and fat fraction (r: -0.7 [-0.9, -0.4]) in the combined parotid glands. There was positive correlation between 11 C-met uptake and stimulated salivary flow (r: 0.5 [0.03, 0.8]) and negative correlation for stimulated salivary flow and fat fraction (r: -0.5 (-0.8, -0.1)] in the parotid glands; similar correlations were also seen in the submandibular glands. There was negative correlation between the global lymphoid aggregation score on minor salivary gland biopsy and the combined salivary gland fat fraction (r: -0.7 [-0.9, -0.2]). Parotid gland SUVmax 18 F- FDG uptake was higher than historical control values (mean: 1.9 g/ml, [SD: 0.5] 1 ) in some patients (pSS mean SUVmax: 2.8 g/mL [SD: 0.8, range 1.7–4.6]), with positive correlation between 18 F– FDG and 11 C-met uptake (r: 0.7 [0.2, 0.9]) in the combined salivary glands. Conclusion: Imaging showed clear differences between pSS and HV and correlated with clinical endpoints. Low 11 C-met uptake and high fat fraction on MRI may indicate poor residual gland function, while high 18 F- FDG and stable 11 C-met uptake may define a subpopulation that responds well to anti-inflammatory therapies. References: [1] Basu S, et al. Nucl Med Commun 2008; 29:367–73. Acknowledgement: Study/editorial support by Fishawack Indicia Ltd, UK funded by GSK. Disclosure of Interests: Michele Bombardieri Grant/research support from: Celgene, Consultant for: Medimmune, Coziana Ciurtin: None declared, Michalis Kostapanos Consultant for: Is an NHS consultant seconded to the GSK Clinical Cambridge Unit (50%) and has nothing to disclose., Elisa Astorri: None declared, Anwar Tappuni: None declared, Natasha Jordan: None declared, Saleem Azeem Shareholder of: GSK, Teresa Fuller Shareholder of: GSK, Employee of: GSK, Kathleen Port Shareholder of: GSK, Employee of: GSK, Nirav Ratia Shareholder of: GSK, Employee of: GSK, Andre van Maurik Shareholder of: GSK, Employee of: GSK, Calum Gray: None declared, Lucy Kershaw: None declared, Rob Janiczek Shareholder of: GSK, Employee of: GSK, Graham Searle: None declared, Paul Galette Shareholder of: GSK, Employee of: GSK, Marius de Groot Shareholder of: GSK, Employee of: GSK, Neel Patel Shareholder of: GSK, Employee of: GSK, Nicolas Wisniacki Shareholder of: GSK, Employee of: GSK, Mats Bergstrom Shareholder of: GSK, Consultant for: acted as external consultant to GSK, Employee of: GSK, Pilar Jimenez-Royo Shareholder of: GSK, Employee of: GSK, Ruth Tarzi Shareholder of: GSK, Employee of: GSK